2021
DOI: 10.3389/fpsyg.2021.762392
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cultural Activities on People With Cognitive Impairment: A Systematic Review

Abstract: Museums and cultural institutions are increasingly striving to respond to the interests and needs of the society that hosts them. This means, apart from other actions, that these institutions must be involved in the health and wellbeing of society, and the creation of cultural activities aimed at people with cognitive impairment, a group of individuals that is growing worldwide due to the aging of society and the increasing prevalence of dementia. The involved sectors are aware of the potential and benefits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 169 publications
2
6
0
Order By: Relevance
“…The statistically significant result obtained for dementia when conducting a partial MA’ considering the CI typologies demonstrated that cultural interventions can be beneficial in some cases. The obtained results can be related to what the precedent SR concluded [ 22 ]. This means that this type of intervention can be beneficial for people living with CI, making their lives more comfortable during the process.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The statistically significant result obtained for dementia when conducting a partial MA’ considering the CI typologies demonstrated that cultural interventions can be beneficial in some cases. The obtained results can be related to what the precedent SR concluded [ 22 ]. This means that this type of intervention can be beneficial for people living with CI, making their lives more comfortable during the process.…”
Section: Discussionsupporting
confidence: 81%
“…The approach this type of intervention can provide to CI patients may be the reason for the statistically significant result, since again, the benefits this type of intervention can provide to the participants are directly related to those outputs related to their emotional wellness more than their clinical well-being [60][61][62]. Again, there is an interrelationship between these meta-analysis results and the ones obtained during the previous SR [22], with the most reported outcomes for performing arts interventions being the ones related to socialization and communication as well as the ones related to emotional well-being. These results reinforce the evidence that cultural interventions have the potential to have a positive impact on non-clinical aspects of CI [58,[63][64][65].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations